Modelling Forest Systems. Workshop on the Interface Between Reality, Modelling and the Parameter Estimation Processes, Sesimbra 2003
DOI: 10.1079/9780851996936.0063
|View full text |Cite
|
Sign up to set email alerts
|

Linking process-based and empirical forest models in eucalyptus plantations in Brazil.

Abstract: The 3-PG model (Landsberg and Waring, 1997) was parameterized to predict potential productivity across 170 000 ha of Eucalyptus grandis hybrid plantation distributed in 19 regions in eastern Brazil. The regions were defined on the basis of meteorological measurements made by automatic weather stations. Mean annual increments estimated by the model for a 6-year rotation were compared with available observations made annually in permanent sample plots (PSPs). The goodness of fit between estimated and observed gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…The partitioning of carbon, fixed during photosynthesis, is imperfectly understood (Landsberg and Gower, 1997;Gholz and Lima, 1997) and therefore, further research should focus on measuring wholeforest fluxes of carbon and water. An improved physiological understanding of carbon partitioning at the stand level could facilitate extrapolation of trial results and decision-making in forest management (Gholz and Lima, 1997;Binkley et al, 2004;du Toit and Dovey, 2005), especially through the use of process-based models (Waring, 2000;Mäkelä et al, 2001;Coops and Waring, 2001;Dye, 2001;Esprey, 2001;Landsberg et al, 2001;Sands and Landsberg, 2002;Almeida et al, 2003Almeida et al, , 2004Binkley et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The partitioning of carbon, fixed during photosynthesis, is imperfectly understood (Landsberg and Gower, 1997;Gholz and Lima, 1997) and therefore, further research should focus on measuring wholeforest fluxes of carbon and water. An improved physiological understanding of carbon partitioning at the stand level could facilitate extrapolation of trial results and decision-making in forest management (Gholz and Lima, 1997;Binkley et al, 2004;du Toit and Dovey, 2005), especially through the use of process-based models (Waring, 2000;Mäkelä et al, 2001;Coops and Waring, 2001;Dye, 2001;Esprey, 2001;Landsberg et al, 2001;Sands and Landsberg, 2002;Almeida et al, 2003Almeida et al, , 2004Binkley et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…However, it is a highly detailed and comprehensive system, specific to current Australian conditions. Previous work with the 3-PG (Physiological Principles Predicting Growth) and the 3-PGS (3-PG using Satellite data) has shown that these models can be used to explore forest dynamics in a wide range of systems (Almeida et al, 2003;Coops and Waring, 2001b;Dye, 2001;Esprey et al, 2004;Landsberg et al, 2001Landsberg et al, , 2003Nightingale et al, 2004;Sands, 2004;Sands and Landsberg, 2002;Waring, 2000). Although NCAS provides a comprehensive capability within Australia, there is still a need for relatively simple, flexible and widely applicable decision support and scenario analysis systems.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of an empirical forest growth model to account for climate change could involve the gradual adjustment of the driving variable used, such as the site index (SI). For example, Almeida et al (2003) linked a process-based model and an empirical growth and yield model, using a relationship between mean annual increment and SI. Matala et al (2005) updated a variable expressing the competition status of the tree using climatic parameters in an empirical growth and yield model (Matala et al 2006).…”
Section: Introductionmentioning
confidence: 99%